2020
DOI: 10.22190/fupes190315049d
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Parameters and Morphological Characteristics of Overweight and Obese Children Aged Seven

Abstract: The aim of the research was to determine the correlation of morphological characteristics and fitness parameters of overweight and obese boys aged seven. The sample of participants consisted of 198 pupils (boys) aged seven years, from elementary schools from the territory of the city of Niš, Paraćin, Bela Palanka, Leskovac and others, classified as a category with increased body mass or obesity. Morphological characteristics were determined by measuring parameters of longitudinal (3), transversal, (3) circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Adipose tissue is endocrinologically active and involved in the interaction between adipocytokines, insulin, and sexsteroid hormones, thereby influencing cardiovascular fitness and metabolic processes (Bunc, 2006). In that regard, Pantelic (2017) considers that excess fat tissue is an obstacle to developing fitness abilities and motor tasks, which is in accordance with another studies (Zivkovic et al, 2018;Dosic et al, 2020), who have identified that children with higher fat mass have worse results in cardiovascular endurance, leg strength, flexibility, and running speed. Hence, overall BMI values are significantly associated with cardiorespiratory fitness, and therefore, multiple included studies have confirmed this statement (Mota et al, 2006;Paschoal et al, 2009;Esmaeilzadeh & Ebadollahzadeh, 2012;Tsiros et al, 2016).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Adipose tissue is endocrinologically active and involved in the interaction between adipocytokines, insulin, and sexsteroid hormones, thereby influencing cardiovascular fitness and metabolic processes (Bunc, 2006). In that regard, Pantelic (2017) considers that excess fat tissue is an obstacle to developing fitness abilities and motor tasks, which is in accordance with another studies (Zivkovic et al, 2018;Dosic et al, 2020), who have identified that children with higher fat mass have worse results in cardiovascular endurance, leg strength, flexibility, and running speed. Hence, overall BMI values are significantly associated with cardiorespiratory fitness, and therefore, multiple included studies have confirmed this statement (Mota et al, 2006;Paschoal et al, 2009;Esmaeilzadeh & Ebadollahzadeh, 2012;Tsiros et al, 2016).…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, there were around 1,887 participants who were obese, whereas around 2,197 were normally weight (except the total participant sample, the rest of the presented numbers should be used with caution). In addition, two studies have included male participants only (Esmaeilzadeh & Ebadollahzadeh, 2012;Dosic et al, 2020), and only one study (Loftin et al, 2001) had female participants only. The other 16 included studies had mixed gender participants.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global increase in overweight and obesity has been evident in recent decades and has become extremely widespread in both developed and developing countries, leading to a modern "obesity epidemic" (Shirasava et al, 2015;Forouzanfar et al 2016;Hurbo et al al., 2018;Psaltopoulou et al, 2019;Đošić et al, 2019). Weight gain has a negative effect on people's physical and mental health (Wasiluk & Saczuk, 2020;Strong et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%